SUMBANGAN KECEPATAN TERHADAP PRESTASI LOMPAT JAUH - SISWO SURYANTO (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2010)
This research will look for an alternative of answer about contribution of speed to achievement of long jump. To find the answer, Writer does research to 40 Study Students of programe Penjaskesrek in 1999 STKIP PARIS BARANTAI KOTABARU. In this research entangles one independent variables that is speed and one dependent variableses that is achievement of long jump. Analysis applied is correlation. Starting from the problems, hence purpose of which will be reached in this research in general is wish to know contribution of speed to achievement of long jump which is one of number jumps at athletic athletics branch. As for peculiarly purpose of this research is to know " How much is big of contribution of speed to achievement of long jump students of Programe Study Penjaskesrek in 1999 STKIP PARIS BARANTAI KOTABARU.This research executed Monday and Tuesday date of 9 and 10 November 2009. After data obtained, process and is analysed result of its is as follows:a. Average Of X ( Speed) = 7,65 and Standard deviation = 0,3195.b. Average Of Y ( Achievement of Long jump) = 4,09 and Standard deviation                = 0,4846.c. With score spread ( X) Minimum Speed 7,25 Maximum 8,80.d. With score spread ( Y) Achievement of Minimum Long Jump 3,20 Maximum    5,00.e. Correlation coefficient between ( X) speed and achievement of long jump ( Y)    = - 0,39 and signifikansi after in Uji t.f. Coefficient of determination equal = 15,21 %.From result of above análisis, after in testing t is obtained [by] t calculate equal = - 2,61,While table t with = 0,05 dk 38 obtained [by] t 0,95 = 1,68 ( interpolation). Based on above kreteria explains t calculate located in outside t tables, or - 2,61 < 1,68 < 2,61. So inferential refused H0 and receives H1 alternative hypothesis or hipótesis job(activity.Thereby hipótesis is expressing " There is big of contribution of speed to achievement of long jump studets of Program Studi Penjaskesrek in 1999 STKIP PARIS BARANTAI KOTABARU" received and signifikansi,equal to 15,21% and there are the factors 84.79%.                                                              Kata-kata kunci:Kecepatan , Prestasi lompat jauh, dan Mahasiswa